Long-range, selective, on-demand suspension interactions: Combining and triggering soluto-inertial beacons - Banerjee, Anirudha (Sci Adv, 2019)
Structures and particles that slowly release solute into solution can attract or repel other particles in suspension via diffusiophoresis, a process we termed “soluto-inertial (SI) interactions.” These SI interactions involve “beacons” that establish and sustain nonequilibrium solute fluxes over long durations. Here, we demonstrate the versatility of the SI concept and introduce distinct strategies to manipulate solute gradients and, hence, suspension behavior using beacons with different physicochemical properties. First, we demonstrate on-demand particle migration using beacons that can be actuated with a trigger. We then show the synergy between multiple, distinct beacons that modify solute fluxes in a way that allows directed, yet selective, colloidal migration to specific target sites. Moreover, this multibeacon harmony enhances migration velocities, and delays the equilibration of the SI effect. The different SI techniques highlighted here suggest previously unidentified possibilities for sorting and separating colloidal mixtures, targeting particle delivery, and enhancing rates of suspension flocculation.